Exploring the Water Crisis and Viability of Unregulated Groundwater in India: An Analysis - Nidhi, Aditi; Charan, J. Lakshmi (Nature environment and pollution technology, 2025)
Water conservation and management are significant features of ancient Indian Vedic culture. However, India’s rapid industrialization, globalization, and urbanization have posed a serious threat to this practice. Many metropolitan cities and other cities will likely have groundwater depletion in the near future. As per the ‘United Nations University - Institute for Environment and Human Security (UNU-EHS)’ report titled “The 2023 Interconnected Disaster Risks Report”, India is close to reaching its tipping point of groundwater depletion. It also highlighted that 27 of 31 major global aquifers are depleting faster than they can be replenished. A combination of factors, including climate change, private land ownership, mechanical pumping, etc., led to the depletion of groundwater and water scarcity for farming and other purposes. Additionally, NITI Aayog and the Central Water Commission have released several reports that highlighted the plight of the country’s aquifers. India’s groundwater resources are not only a potential source for agricultural, domestic, and industrial needs in the country but also a threat to its sustainable development and equitable distribution. At present, there is no central law on the groundwater regulation. Although the Model Groundwater (Sustainable Management) Bill 2017 is an affirmative step, its effectiveness depends on implementation by state governments, the establishment of robust local institutions, and removing political incentives from groundwater management. Until now, landowners have enjoyed monopolistic access to groundwater due to common laws that recognize uncontrolled rights over the resources. These restrictions have perpetuated gross inequities in accessing groundwater, which makes a remarkable shift from previous laws. This paper evaluates India’s existing groundwater laws to achieve sustainability, equity, and the effective execution of water rights. It also delves into the lacunae in the existing laws and suggestive measures to control the challenges of groundwater in India.